1991
DOI: 10.1002/pssb.2221670207
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Hydrogen Centres in LiF–H and LiF–H, Mg2+ Crystals

Abstract: Atomic hydrogen centres in LiF–H− and LiF–H−, Mg2+ are studied by optical and ESR techniques. X‐irradiation of these crystals at 80 K leads to the formation of the H io‐centres which are thermally stable up to 110 K. After thermal annealing of the H io‐centres in LiF–H−, Mg2+ crystals a new atomic hydrogen centre is observed which is interpreted as an interstitial hydrogen atom stabilized by a complex of the Mg2+ ion and a positive ion vacancy (H io(Mg)‐centre). Thermal decay of the (H io(Mg)‐centres occurs at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In our previous paper [9] we found that X-irradiation of LiF-H-crystals at 80 K leads to the creation of atomic hydrogen centres, which have a doublet ESR spectrum with splitting between lines of 518 x T. The observed two proton H F lines were inhomogeneously broadened by unresolved SHF interactions and the linewidth AB (peak to peak) was 45 x T. However, recently we found, using crystals with higher hydrogen concentration (lo2' ~r n -~) that these centres saturate readily at 80 K and the decrease of microwave power leads to the appearance of the SHF structure. A similar ESR spectrum was first observed in y-irradiated LiF-OH-by Akhvlediani et al [lo] who assigned the ESR signal to the unperturbed hydrogen atom in a cation vacancy (HEc centre).…”
Section: Esrmentioning
confidence: 94%
See 2 more Smart Citations
“…In our previous paper [9] we found that X-irradiation of LiF-H-crystals at 80 K leads to the creation of atomic hydrogen centres, which have a doublet ESR spectrum with splitting between lines of 518 x T. The observed two proton H F lines were inhomogeneously broadened by unresolved SHF interactions and the linewidth AB (peak to peak) was 45 x T. However, recently we found, using crystals with higher hydrogen concentration (lo2' ~r n -~) that these centres saturate readily at 80 K and the decrease of microwave power leads to the appearance of the SHF structure. A similar ESR spectrum was first observed in y-irradiated LiF-OH-by Akhvlediani et al [lo] who assigned the ESR signal to the unperturbed hydrogen atom in a cation vacancy (HEc centre).…”
Section: Esrmentioning
confidence: 94%
“…The experimental technique and the preparation of the crystals have been described elsewhere [9]. The LiF-H-crystals used in this work contained 1017 to lo2' U centres, and the concentration of U centres in NaF-H-crystals range from l O I 7 to lo1* ~m -~.…”
Section: Experimental Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The experimental technique and the preparation of the crystals have been described elsewhere [3,4].TheLiF-H-,Mg2+ crystalsusedinthisworkdidnotcontainmorethan3 x 10" cm-3 U-centres (the intensity of the U absorption band at 9.7 eV is less than 100 cm-' [4,51). The concentration of MgF, ranged from 0.05 to 0.1 wt% in the melt.…”
Section: Experimental Techniquementioning
confidence: 99%
“…In our previous paper [3] we have reported the results of investigations of LiF-H-, Mg2+ crystals after X-irradiation at 80 K and subsequent heating to room temperature and above. Two types of atomic hydrogen centres connected with magnesium-vacancy dipoles were observed.…”
Section: Introductionmentioning
confidence: 99%